2015
DOI: 10.5963/ijep0501006
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality Assessment for Different Land Use in the Panchase Area of Western Nepal

Abstract: Abstract-Soil quality management helps to maintain biological productivity; air and water quality; and human habitation and health. As improper land management can deteriorate soil function, the evaluation of soil quality for different land use is necessary. To evaluate soil quality for different land use types in the Panchase area, soil quality index was computed on the basis of the soil management assessment framework. Protected forest has the highest soil quality index (0.95) followed by community forest (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
4
22
2
Order By: Relevance
“…Slightly higher pH in forest soil might be due to the higher OM of the site and soil derived from the calcareous rocks such as limestones, sandstones, and parent materials of the area. The result of the study was different from the Kalu et al (2015) who reported that higher level of pH in bari and pasture than in the forest in Panchase area of western Nepal. This may be due to the forest was dominated by Shorea robusta forest which characterized the presence of high pH (> 6.5) base rich soil (Amatya et al, 2016).…”
Section: Effect Of Land Uses On Soil Properties Under Studycontrasting
confidence: 98%
“…Slightly higher pH in forest soil might be due to the higher OM of the site and soil derived from the calcareous rocks such as limestones, sandstones, and parent materials of the area. The result of the study was different from the Kalu et al (2015) who reported that higher level of pH in bari and pasture than in the forest in Panchase area of western Nepal. This may be due to the forest was dominated by Shorea robusta forest which characterized the presence of high pH (> 6.5) base rich soil (Amatya et al, 2016).…”
Section: Effect Of Land Uses On Soil Properties Under Studycontrasting
confidence: 98%
“…The SMAF has also been successfully used in several other countries around the world [e.g., South Africa (Swanepoel et al, 2015), Ethiopia (Gelaw et al, 2015), Nepal (Kalu et al, 2015)]. The first SMAF application to Brazilian tropical soils was conducted by Cherubin et al (2016a), who verified that SMAF was effective for assessing SQ changes due to land-use change (LUC) for sugarcane expansion in the central-southern region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SMAF has been tested in other countries around the world, including South Africa (Swanepoel et al, 2015), Ethiopia (Erkossa et al, 2007;Gelaw et al, 2015), and Nepal (Kalu et al, 2015). Data from Brazilian soils was limited in the development and validation of the SMAF, and to our knowledge, no other studies using SMAF as a tool for assessing the impacts of current management practices and land uses on SQ in Brazil have been published.…”
mentioning
confidence: 99%